2003
DOI: 10.1093/toxsci/kfg228
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Pulmonary Toxicity Assessment of Single-wall Carbon Nanotubes in Rats

Abstract: The aim of this study was to evaluate the acute lung toxicity of intratracheally instilled single-wall carbon nanotubes (SWCNT) in rats. The lungs of rats were instilled either with 1 or 5 mg/kg of the following control or particle types: (1) SWCNT, (2) quartz particles (positive control), (3) carbonyl iron particles (negative control), (4) phosphate-buffered saline (PBS) + 1% Tween 80, or (5) graphite particles (lung tissue studies only). Following exposures, the lungs of PBS and particle-exposed rats were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
655
5
10

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,353 publications
(701 citation statements)
references
References 12 publications
31
655
5
10
Order By: Relevance
“…The research covering the new types of NPM is limited and the number of studies of the environmental impacts of NPM are few. Carbon nanotubes have been shown to cause granulomas in the lungs of animals, an immunological response to foreign objects (Lam et al, 2004;Warheit et al, 2004;Muller et al, 2005;Shvedova et al, 2005), and was found in one study to be more toxic than carbon black and quartz (Lam et al, 2004). Fullerenes have been shown in studies to be bioavailable when released in aqueous environments, cause lipid peroxidation in fishbrain (Oberdorster, 2004a) and inhibit bacterial growth (Fortner et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The research covering the new types of NPM is limited and the number of studies of the environmental impacts of NPM are few. Carbon nanotubes have been shown to cause granulomas in the lungs of animals, an immunological response to foreign objects (Lam et al, 2004;Warheit et al, 2004;Muller et al, 2005;Shvedova et al, 2005), and was found in one study to be more toxic than carbon black and quartz (Lam et al, 2004). Fullerenes have been shown in studies to be bioavailable when released in aqueous environments, cause lipid peroxidation in fishbrain (Oberdorster, 2004a) and inhibit bacterial growth (Fortner et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms for the lack of continued embryo development remained unknown. Studies in other cell types have shown that internalized nanoparticles [7] derived from materials other than that tested here disrupted fibroblast and cancer cells after adhering to the cell membranes, impaling and/or releasing toxic ions [27][28][29][30][31][32]. Moreover, nanoparticles internalized into cells increased the reactive oxygen species (ROS), elevated intracellular calcium, activated transcription factors [10] and initiated apoptosis or cell death [14].…”
Section: Discussionmentioning
confidence: 92%
“…In a study of SWCNTs instilled into the lungs of rats, multi-focal granulomas (without transient inflammation or persistent lesions) were observed at doses of 1 or 5 mg / kg body weight [Warheit et al 2004]. In a study of mice instilled with one of several types of SWCNTs (i.e., raw, purified, iron-containing, and nickel-containing) at doses of 0.1 or 0.5 mg/mouse (approximately 3 or 16 mg/kg body weight), dose-dependent epithelioid granulomas were observed at 7 days, which persisted at 90 days [Lam et al 2004[Lam et al , 2006.…”
Section: Carbon Nanotubesmentioning
confidence: 99%